Saffron Pre-Treatment Promotes Reduction in Tissue Inflammatory Profiles and Alters Microbiome Composition in Experimental Colitis Mice - Suhrid Banskota; Hassan Brim; Yun Han Kwon; Gulshan Singh; Sidhartha R. Sinha; Huaqing Wang; Waliul I. Khan; Hassan Ashktorab (Molecules, 2021)
Inflammatory bowel disease (IBD) is a chronic inflammatory condition of the gastrointestinal tract with an incompletely understood pathogenesis. Long-standing colitis is associated with increased risk of colon cancer. Despite the availability of various anti-inflammatory and immunomodulatory drugs, many patients fail to respond to pharmacologic therapy and some experience drug-induced adverse events. Dietary supplements, particularly saffron (Crocus sativus), have recently gained an appreciable attention in alleviating some symptoms of digestive diseases. In our study, we investigated whether saffron may have a prophylactic effect in a murine colitis model. Saffron pre-treatment improved the gross and histopathological characteristics of the colonic mucosa in murine experimental colitis. Treatment with saffron showed a significant amelioration of colitis when compared to the vehicle-treated mice group. Saffron treatment significantly decreased secretion of serotonin and pro-inflammatory cytokines, such as TNF-α, IL-1β, and IL-6, in the colon tissues by suppressing the nuclear translocation of NF-κB. The gut microbiome analysis revealed distinct clusters in the saffron-treated and untreated mice in dextran sulfate sodium (DSS)-induced colitis by visualization of the Bray–Curtis diversity by principal coordinates analysis (PCoA). Furthermore, we observed that, at the operational taxonomic unit (OTU) level, Cyanobacteria were depleted, while short-chain fatty acids (SCFAs), such as isobutyric acid, acetic acid, and propionic acid, were increased in saffron-treated mice. Our data suggest that pre-treatment with saffron inhibits DSS-induced pro-inflammatory cytokine secretion, modulates gut microbiota composition, prevents the depletion of SCFAs, and reduces the susceptibility to colitis.